2018
DOI: 10.1002/cam4.1675
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitination and stabilization of programmed cell death ligand 1 by ubiquitin‐specific peptidase 9, X‐linked in oral squamous cell carcinoma

Abstract: BackgroundThe immune checkpoint protein programmed cell death ligand 1 (PD‐L1) binds to PD1 to promote tumor cell escape from the killing effect of the immune system. However, there are few studies on the regulatory mechanisms of PD‐L1 in tumors. Although PD‐L1 has been reported to undergo ubiquitination in some cancers, its regulatory mechanisms in oral squamous cell carcinoma (OSCC) are unclear. Therefore, we aimed to investigate this phenomenon.MethodsWe examined the expression and function of USP9X and PD‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…To overcome the clinical response problem, it is crucial to find the upstream regulator that may modulate the amount of PD-L1 in GC 31 , 32 . Hence, deubiquitinase attracted our eyes as there have been three deubiquitinases reported to stabilize PD-L1, including COP9 signalosome 5 (CSN5), ubiquitin specific peptidase 9 X-linked (USP9X) and ubiquitin specific peptidase 22 (USP22) 33 , 34 , 35 . Nevertheless, correlation analysis using GEPIA ( http://gepia.cancer-pku.cn ) 36 indicated that PD-L1 is not correlated with CSN5, USP9X and USP22 in GC ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome the clinical response problem, it is crucial to find the upstream regulator that may modulate the amount of PD-L1 in GC 31 , 32 . Hence, deubiquitinase attracted our eyes as there have been three deubiquitinases reported to stabilize PD-L1, including COP9 signalosome 5 (CSN5), ubiquitin specific peptidase 9 X-linked (USP9X) and ubiquitin specific peptidase 22 (USP22) 33 , 34 , 35 . Nevertheless, correlation analysis using GEPIA ( http://gepia.cancer-pku.cn ) 36 indicated that PD-L1 is not correlated with CSN5, USP9X and USP22 in GC ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Casitas B-lineage lymphoma (Cbl) family has three major isoforms, c-Cbl, Cbl-b, and Cbl-c, among which c-Cbl and Cbl-b with a ubiquitin-associated (UBA) domain suppressed PD-L1 expression after inhibiting PI3K/Akt, JAK-STAT, and MEK/Erk signaling pathways in NSCLC [ 140 ]. Additionally, ubiquitin-specific peptidase 22 (USP22) in HCC [ 141 ], ubiquitin-specific peptidase 9, X-linked (USP9X) in OSCC [ 142 ], and ubiquitin C-terminal hydrolase L1 (UCHL1) in NSCLC [ 143 ] deubiquitinate and upregulate the PD-L1 expression.…”
Section: Regulation Of Pd-l1 At Protein Levelmentioning
confidence: 99%
“…ese studies suggest that targeting PD-L1 ubiquitination may be an alternative way to improve immune checkpoint therapy. In oral squamous cell cancer (OSCC), ubiquitin-specific peptidase 9, X-linked (USP9X) was found to be upregulated and protected PD-L1 from ubiquitination and degradation, leading to high protein level of PD-L1, resulting in the failure of checkpoint blockade [33]. Abnormal ubiquitination is usually catalyzed by the mutation or ectopic expression of genes that encode E3 ubiquitin ligases or deubiquitinases [34].…”
Section: Ubiquitinationmentioning
confidence: 99%